Systemic Induction of Photosynthesis via Illumination of the Shoot Apex Is Mediated Sequentially by Phytochrome B, Auxin and Hydrogen Peroxide in Tomato . Issue 2 (22nd August 2016) - Guo, Zhixin; Wang, Feng; Xiang, Xun; Ahammed, Golam Jalal; Wang, Mengmeng; Onac, Eugen; Zhou, Jie; Xia, Xiaojian; Shi, Kai; Yin, Xueren; Chen, Kunsong; Yu, Jingquan; et al.
Abstract : Red light perceived in the shoot apex by phyB alters IAA and H2 O2 signaling, accelerating photosynthetic induction in systemic leaves by increasing CEF-dependent ATP production in tomato. Abstract: Systemic signaling of upper leaves promotes the induction of photosynthesis in lower leaves, allowing more efficient use of light flecks. However, the nature of the systemic signals has remained elusive. Here, we show that preillumination of the tomato ( Solanum lycopersicum ) shoot apex alone can accelerate photosynthetic induction in distal leaves and that this process is light quality dependent, where red light promotes and far-red light delays photosynthetic induction. Grafting the wild-type rootstock with a phytochome B ( phyB ) mutant scion compromised light-induced photosynthetic induction as well as auxin biosynthesis in the shoot apex, auxin signaling, and RESPIRATORY BURST OXIDASE HOMOLOG1 ( RBOH1 )-dependent hydrogen peroxide (H2 O2 ) production in the systemic leaves. Light-induced systemic H2 O2 production in the leaves of the rootstock also was absent in plants grafted with an auxin-resistant diageotropica ( dgt ) mutant scion. Cyclic electron flow around photosystem I and associated ATP production were increased in the systemic leaves by exposure of the apex to red light. This enhancement was compromised in the systemic leaves of the wild-type rootstock with phyB and dgt mutant scions and also in RBOH1 -RNA interference leaves with the wild type as scion. Silencing of ORANGE RIPENING, which encodes NAD(P)H dehydrogenase, compromised the systemic induction of photosynthesis. Taken together, these results demonstrate that exposure to red light triggers phyB-mediated auxin synthesis in the apex, leading to H2 O2 generation in systemic leaves. Enhanced H2 O2 levels in turn activate cyclic electron flow and ATP production, leading to a faster induction of photosynthetic CO2 assimilation in the systemic leaves, allowing plants better adaptation to the changing light environment.